Mentawai Taro Corm Flour’s Benefits on Hyperglycemia and Pancreas Histopathology in Diabetic Mice - Aini, Wardatul; Santoso, Putra; Rahayu, Resti (Jurnal Biologi Tropis, 2024)
Diabetes mellitus (DM) is among the most severe health issues globally. This study aimed to determine the beneficial effects of Mentawai taro (Colocasia esculenta var. Mentawai) in managing hyperglycemia and attenuating inflammation in pancreatic ß-cells in alloxan-induced diabetic mice. Twenty-one adult male mice were divided into three groups: healthy (non-DM), alloxan-induced DM, and DM mice fed with a diet containing 25% Mentawai taro flour. The treatments were administered for four consecutive weeks. Various parameters, including blood glucose levels, glucose tolerance, and insulin tolerance, were assessed, alongside microscopic examination of pancreatic histology. The results demonstrated that supplementation with 25% Mentawai taro corm significantly lowered fasting blood glucose levels (**P<0.01) and improved glucose tolerance (*P<0.05) and insulin tolerance (*P<0.05) compared to untreated diabetic mice. Mentawai taro corm also ameliorated pancreatic degeneration, as indicated by a larger islet of Langerhans area, a higher total cell number per islet, and a significantly lower number of degenerated cells in pancreatic tissue (**P<0.01). In conclusion, supplementing Mentawai taro corm at 25% in the diet could effectively help manage diabetic issues, including hyperglycemia and pancreatic degeneration.